Market-based renewables: How flexible hydrogen electrolyzers stabilize wind and solar market values - Oliver Ruhnau (ZBW - Leibniz Information Centre for Economics, 2020)
Wind and solar energy are often expected to fall victim to their own success: the higher their share in electricity production, the more their revenue on electricity markets (their “market value”) declines. While in conventional power systems, the market value may converge to zero, this study demonstrates that “green” hydrogen production, through adding electricity demand in low-price hours, can effectively and permanently halt the decline. With an analytical derivation, a Monte Carlo simulation, and a numerical electricity market model, I find that – due to flexible hydrogen production – market values in 2050 likely converge above exteuro19 ± 9 per MWh for solar energy and above exteuro27 ± 8 per MWh for wind energy. This is in the range of the projected levelized costs of renewables and has profound implications. Market-based renewables may hence be within reach.
Additional information: Please cite as: Ruhnau, Oliver (2021): “How flexible electricity demand stabilizes wind and solar market values: The case of hydrogen electrolyzers”, Applied Energy, https://doi.org/10.1016/j.apenergy.2021.118194; More recent version: https://doi.org/10.1016/j.apenergy.2021.118194
Keywords: Q4; Q40; Q41; Q42; 330; Renewable energy; Hydrogen electrolysis; Electricity market; Electricity economics; Integrated energy system; Flexible electricity demand